The Development of a Model of Inducing Nationalist-Religious Characters in Islamic Boarding School in SMP 6 Kedungsuren Kendal Regency to Anticipate Radicalism among Young Generation - Sriyanto, Sriyanto; Kurniawan, Edi; Suharini, Erni; Syifauddin , Mohammad (KnE Social Sciences, 2019)
Globalization is a phenomenon where the world seems small while the interaction and interdependence among all countries in the world gets more intensive including Indonesia. Beside leading to positive effect, this circumstance also causes negative impact such as national disintegration threats. Those threats relate to many foreign ideologies and cultures entering to Indonesia so the values of Indonesian ideologies became degradable. The emerging threats and interferences are mostly based on ideologiesandreligioninthesakeofpeople’sprosperity.Therecentconditionrequires the importance of revitalizing the values of ideology and culture of Indonesia that can be conducted through national-religious character education which has been induced to people since their childhood one of which through Islamic boarding school. The research was conducted in SMP NU 06 Kedungsuren, Kaliwungu Selatan District, Kendal Regency, Central Java Province. The purpose of this research is to develop the model of inducing nationalist-religious character education in Islamic boarding school that can be applied as a media to decrease or suppress the radicalism threats among young generation. This recent study belongs to qualitative research using R&D research design conducted by applying observation, documentation and interview to the students, teacher, head of foundation, and the principal to ﬁnd out the educational processinIslamicboardingschool.Afterthat,thebaseofdataandmodelwerecreated. The result of this research is a model of inducing the appropriate nationalist-religious character education implemented in Islamic boarding school. Keywords: the model of inducing character, nationalist-religious, Islamic boarding school, SMP NU 06 Kedungsuren